2014
DOI: 10.5430/mos.v1n2p23
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Leadership and Communication Skills of Nurse Managers and the Organizational Citizenship Behaviors of Medical-Surgical Nurses and Nursing Assistants

Abstract: This quantitative research study, with a correlation design, used an online survey to determine if a positive correlation existed between the leadership and communication skills of nurse managers and the organizational citizenship behaviors of the nurses and nursing assistants who work on the medical-surgical nursing units of a community hospital in Northern New Jersey. The predictor variables were the employee's perceptions of their nurse manager leadership and communication skills and the self-reported organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…In line with this study, the findings of other studies pointed to variables mentioned above. 6,[44][45][46][47][48][49] The nurse leaders' effective relations with staff along with empathy predispose to confidence and assurance. The ethical leaders should be cautious with what they say and do as they should acquire the subordinates' confidence.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this study, the findings of other studies pointed to variables mentioned above. 6,[44][45][46][47][48][49] The nurse leaders' effective relations with staff along with empathy predispose to confidence and assurance. The ethical leaders should be cautious with what they say and do as they should acquire the subordinates' confidence.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the study of Norouinia et al (2015) which evaluated the viewpoints of nurses in Iran showed that heavy workload, shortage in nursing personnel, and insufficient time were the main important suggested barriers by the nurses (19). Furthermore, it is believed that professional communicational skill is required for establishing efficient relationships and lack of such skills could have negative effects on the nurses as well as the performance of their team (26,28). In this regard, the participants of a study indicated the importance of team work in providing care for patients, effective cooperation with each other, and their role in occupational and moral satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the study of Cullen and Gordon (2014) stated that nursing managers are effective leaders and their communication skills would affect the organizational behaviors of the nursing team (26). Similarly, Vermeir (2018) reported that 68% of the nurses were satisfied with the communicational manner of the managers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The researchers also emphasized on the relationship between supervisors and subordinates to decrease and cope up with stress. The significance of trustworthy and open communication culture between leader and member and role modeling of open communication by the managers were also highlighted by Cullen and Gordon (2014). Their findings revealed that nurse managers with effective leadership and communication skills helped enhance the organizational citizenship behaviors of the nursing team.…”
Section: Communication Job Satisfaction Employee Engagement and Citmentioning
confidence: 98%